Lafẓ “Al-Auliyā'” baina an-Naṣṣ wa al-Wāqi‘: Dirāsah Dalāliyyah - Hatta Raharja (Alfaz (Arabic Literatures for Academic Zealots), 2022)
This article examines the condition of Jakarta's residents in late 2016 and early 2017. Some Muslims in Jakarta were able to mobilize a movement they dubbed "Aksi Bela Islam" after viewing video recordings of the then-leader's words that were distributed via media networks and other means. They may have clashed after viewing the footage, prompting Jakartans, organizations, and associations to convene and ask the Indonesian Ulema Council to address the issue. The respondents requested the opinion of the Indonesian Ulema Council regarding the ruler's statement, “... that you deny verse 51 of Surah Al-Mā'idah ..,” where the controversial word is “auliyā'” The words have multiple meanings due to the fact that they themselves have multiple meanings. These words have multiple meanings, as interpreters may interpret them differently, and there are also contradictions and contradictions between litigants and justices in interpreting these words. From this point on, the researcher will seek linguistic issues associated with this incident and avoid mentioning political issues. The researcher analyzes it by analyzing the elements of semantic meaning with the aid of the opinions of commentators and translators regarding the verse in question, the dictionaries considered, and the words of scholars who support and do not support the interpretation. This article will inform you of the tendency of the Indonesian Ulema Council to issue fatwas on linguistic matters.